Men and Masculinities from Matricultural Perspectives: An Introduction - Jung, Patrick J. (Matrix, 2025)
This special issue of Matrix: A Journal for Matricultural Studies examines the lives of men from matricultural perspectives. Matriculture is a concept derived from the interpretive anthropology of Clifford Geertz, who developed his cultural systems theory based on an understanding of the symbolic elements that constitute human cultures. Marie-Françoise Guédon, Linnéa Rowlatt, and Angela Sumegi have further defined matriculture as those aspects of a cultural system unique to women. The articles, interviews, and book reviews in this special issue illustrate two trends that warrant further investigation. First, men play crucial roles in the creation, performance, and maintenance of matricultures. Second, the interviews published in this special issue indicate that women in Indigenous societies have historically played essential roles in preserving, revitalizing, and decolonizing their cultures. Moreover, women continue this vital work in today's world, regardless of whether they hail from societies that possess matrilineal, patrilineal, or bilateral kinship systems.